Theoretical analysis on the wind power and pumped hydropower storage integrated flood mitigation system - Siti Aishah, Safi (2019)
The immediate consequences of flood causes loss of human life and damage to property. The current flood mitigation was more on the urgent need to provide immediate flood relief works. Thus, integrating flood reservoir with pumped hydropower storage seems a promising solutions for flood problems. Pumped hydropower storage is basically known as a storage device that can improve the reliability of the intermittent source of wind energy. But, there is an issue with the cost of a wind power pumped hydropower storage (WPHS) as it can be expensive to construct. Thus, WPHS requires an additional value so that it is worth to construct this storage facility. The reservoir of WPHS can store huge amount of water and if it is designed with similar mechanism of flood reservoir, it may be capable to mitigate flood during extreme hydrological events and render significant benefits, especially in the terms of economic aspects. Due to the feasibility of WPHS reservoir in flood mitigation and the high cost of the projects, it is beneficial to study economic and environmental aspects of WPHS. Thus, this research aims to evaluate economic and environmental performances of wind-power pumped hydropower storage integrated flood mitigation system. The Hybrid Optimization Model for Electric Renewable (HOMER) software was used to simulate and compare power generation system with and without the flood reservoir. Then, the economic aspects of each system were evaluated based on the Net Present Cost (NPC) and Levelized Cost of Energy (LCOE). Meanwhile, environmental impacts were evaluated based on the amount of air pollutants released to the environment. It was found that the estimated volume of the reservoir to attenuate flood event was 8,396,256 m3 and the proposed power system was estimated to support 69% of energy demand in one of the flood-prone areas with a mean value of power output being 0.7 MW and power input 1.2 MW. Based on the simulation in HOMER, the grid standalone system (B-I) which is without flood reservoir is the optimum system with the NPC only RM 0.38 million and the LCOE RM 0.246/kWh. But, when the cost of flood losses are internalised in the total NPC, the wind-diesel with reservoir storage system (A-III) and the wind-grid with the pumped hydro storage system (B-III) will have much lower NPC than other systems that do not include reservoir for flood mitigation. The NPC for system A-III is RM 1.52 million and for system B-I is RM 1.37 million; meanwhile, the NPC for system B-I is RM 10.4 million when the cost of flood losses are included in the total NPC. Between both energy systems which included the reservoir in their design, the amount of pollutants emitted by the A-III system is 408 kg of carbon dioxide per year which is much less than the B-III system which is 29,662 kg of carbon dioxide during similar period. Therefore, it can be said that the A-III system is the most optimum power generation system as it offers benefits in both economic and environmental aspects. But, the suggested size of reservoir for A-III only can capture 20.8 % of excess runoff generated from the whole Pahang basin. It is almost impossible to expect only a reservoir to capture all excess runoff generated from a large basin. A few reservoir can be built at each sub basin to capture the excess runoff as a flood prevention. In conclusion, the WPHS integrated with flood mitigation system seems beneficial in the term of economic and environment.